Allosteric signal transmission in the nucleotide-binding domain of 70-kDa heat shock protein (Hsp70) molecular chaperones - Zhuravleva, Anastasia (National Academy of Sciences, 2011)
The 70-kDa heat shock protein (Hsp70) chaperones perform a wide array of cellular functions that all derive from the ability of their N-terminal nucleotide-binding domains (NBDs) to allosterically regulate the substrate affinity of their C-terminal substrate-binding domains in a nucleotide-dependent mechanism. To explore the structural origins of Hsp70 allostery, we performed NMR analysis on the NBD of DnaK, the Escherichia coli Hsp70, in six different states (ligand-bound or apo) and in two constructs, one that retains the conserved and functionally crucial portion of the interdomain linker (residues [Image: see text]) and another that lacks the linker. Chemical-shift perturbation patterns identify residues at subdomain interfaces that constitute allosteric networks and enable the NBD to act as a nucleotide-modulated switch. Nucleotide binding results in changes in subdomain orientations and long-range perturbations along subdomain interfaces. In particular, our findings provide structural details for a key mechanism of Hsp70 allostery, by which information is conveyed from the nucleotide-binding site to the interdomain linker. In the presence of ATP, the linker binds to the edge of the IIA β-sheet, which structurally connects the linker and the nucleotide-binding site. Thus, a pathway of allosteric communication leads from the NBD nucleotide-binding site to the substrate-binding domain via the interdomain linker.